2009
DOI: 10.1021/ef9000488
|View full text |Cite
|
Sign up to set email alerts
|

Modeling NO−Char Reaction at High Temperature

Abstract: Five Chinese coal chars were prepared in a flat flame flow reactor that can simulate the conditions of real pulverized coal combustion. The kinetics of the NO-char reaction at 1273, 1373, 1473, and 1573 K was studied in a drop tube furnace. A new model of the high-temperature NO-char reaction that took into account the pore diffusion and thermal annealing of char was proposed. The NO-char reaction was predicted by a combination of the model and computational fluid dynamics. Through the comparison of experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…While the heterogeneous pathway of NO reduction has been less investigated than the homogeneous pathway, many investigations explore the kinetics and mechanism of the heterogeneous NO–char reaction. Jensen et al and Zhang et al explored the effects of reaction temperature. , Chambrion et al demonstrated a route to N 2 formation from NO by using isotopic labeling of gases and found that N 2 forms from a combination of a surface nitrogen species and the nitrogen from gaseous NO . Chan et al reported the study of the NO–char reaction and found that the reaction rate is first order in NO concentration in addition to exploring the effects of O 2 on the NO–char reduction reaction .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the heterogeneous pathway of NO reduction has been less investigated than the homogeneous pathway, many investigations explore the kinetics and mechanism of the heterogeneous NO–char reaction. Jensen et al and Zhang et al explored the effects of reaction temperature. , Chambrion et al demonstrated a route to N 2 formation from NO by using isotopic labeling of gases and found that N 2 forms from a combination of a surface nitrogen species and the nitrogen from gaseous NO . Chan et al reported the study of the NO–char reaction and found that the reaction rate is first order in NO concentration in addition to exploring the effects of O 2 on the NO–char reduction reaction .…”
Section: Introductionmentioning
confidence: 99%
“…Their experimental data indicated that lower-rank coal chars were more reactive than higher-rank coal chars. Zhang et al 12 studied five Chinese coal char samples and developed a kinetic model to describe the NO−char reaction behavior and normalize the reactivity of chars with different ranks at high temperature (1273−1573 K). Cances et al 10 reported that the NO reactivity of different solid fuels largely depends on the fuel rank, and the two pathways of NO reduction are competing and predominant at different residence times.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The generated NOx diffuses, and some are adsorbed on the surface of coke particles to react with their active groups. Combined with previous experiments [21,35,36] and simulation studies, the reaction of NO with coke particles at high temperature is the first-order reaction of NO. The reaction equation of coke particle with NO is Char-C+NO→N 2 +C(O).…”
Section: Nox Reduction Modelmentioning
confidence: 67%
“…The detail information about this experiment setup was presented in elsewhere. 34,35 R-form or H-form coal samples were fed into the drop-tube reactor at 12 g h À1 with pure argon as carrying gas (purity 99.999% in volume). The temperature of the reactor was set at 900 C, and under such condition, the sample particles would be heated at a heating rate of 10 4 K s À1 .…”
Section: Preparation Of Char Samplesmentioning
confidence: 99%